APPLYING THE ANALYTIC HIERARCHY PROCESS TO RANK CITY-BRANCHES - Cvetkoska, Violeta; Begicevic Redzep, Nina (My University, 2016)
The aim of the paper is to present developed AHP model for ranking city-branches of a bank. According to the number of active counters the city-branches of the bank are classified into the following three groups: group A with 1-3 active counters, group B with 2-5 active counters and group C with 4-9 active counters. The developed AHP model consists of a goal, criteria and alternatives. The goal is to rank the citybranches in the groups they belong to. The 8 criteria that are defined in the model are: denar savings, foreign currency savings, transaction accounts, exchange operations, public services, master cards, fees for payment operations (commission), and domestic payment operations. The alternatives are the city-branches that belong to each group. Developed AHP model is validated for ranking the city-branches of Commercial bank AD Skopje which are located in Skopje. The programming tool Super Decisions is used to implement the AHP model and the programming tool Expert Choice is used to perform sensitivity analysis. The obtained results are presented and analyzed in the paper.
Keywords: multi-criteria decision-making, Analytic Hierarchy Process, ranking, sensitivity analysis, bank, city-branches